PENERAPAN FUZZY LOGIC CONTROL DENGAN METODE SUGENO UNTUK PENGONTROLAN JUMLAH VOLUME KELUARAN MOTOR MINI WATER PUMP PADA ALAT PENGONTROL PH AIR AKUAPONIK - Mohammad Reza Ar-Ridho; Bambang Siswojo; Eka Maulana (Jurnal Mahasiswa TEUB, 2023)
Water quality is one of the factors that must be considered so that the aquaponic system runs well. One of the important parameters in maintaining water quality is the degree of acidity (pH). Therefore, it is necessary to monitor and control the pH regularly. Control is carried out by adding a buffer solution to the aquaponic pond using a pump motor. Poor water pump performance can result in the incorrect addition of buffer solution according to the required calculation. Controlling the output volume of a mini water pump motor using the Sugeno fuzzy logic method aims to control the volume released according to predetermined calculations. From the research results, the system is able to control the pump output volume according to several predetermined setpoints, namely 25–350 mL with a maximum error steady state of 1% within 1.5–11.8 seconds by adjusting the speed of the pump motor according to the desired amount of solution.Keywords: pH, Fuzzy Logic Sugeno, mini water pump, setpoint